Short-cut nitrogen removal from high-strength ammonia wastewater in a sequencing batch biofilm reactor: roles of NO and its production mechanism - Zhao, Junkai; Zhang, Ju; Yu, Heng; Yang, Wenjuan; Zhao, Jianqiang; Lei, Shuhan; Yang, Jie (Frontiers in Microbiology, 2025)
Nitric oxide (NO) is a key intermediate in the biological nitrogen removal process. However, its role and production mechanism is still not fully understood. In this study, a sequencing batch biofilm reactor (SBBR) was used to study the short-cut nitrogen removal from high-strength ammonia wastewater and NO production mechanism. The ammonia concentration in SBBR was 1,000 mg-N/L, with a carbon-nitrogen ratio of 5, the simultaneous partial nitrification and denitrification efficiency reached 66.42%, while the average total inorganic nitrogen removal efficiency was 83.37 ± 6.93%. Microbial community analysis showed the vital role of functional bacteria such as Thauera, Stappia, and Nitrosomonas in the short-cut nitrogen removal process. The accumulation of NO occurred mainly under aerobic conditions, with the highest NO concentration of 0.19 mg-N/L. NO accumulation was mainly attributed to the incomplete oxidation of hydroxylamine, nitrifier denitrification and heterotrophic denitrification. Synergistic inhibition of nitrite-oxidizing bacteria by NO with free ammonia and free nitrous acid contributed to rapid establishment of partial nitrification and long-term stability of the process. The present study provides novel insights into the underlying mechanisms mediating the inhibition of nitrite-oxidizing bacteria.